LATE CRETACEOUS ARC AND BACK-ARC FORMATION WITHIN THE SOUTHERN NEOTETHYS: WHOLE-ROCK, TRACE ELEMENT AND Sr-Nd-Pb ISOTOPIC DATA FROM BASALTIC ROCKS OF THE YUKSEKOVA COMPLEX (MALATYA- ELAZIG, SE TURKEY) - Ural, Melek; Arslan, Mehmet; Goncuoglu, M. Cemal; Tekin, U. Kagan; Kurum, Sevcan (Ofioliti, 2015)
The remnants of the Southern Neotethys are represented by ophiolitic bodies and subduction/accretion complexes along the Southeast Anatolian-Zagros suture belt in the Eastern Mediterranean. Around Malatya and Elazig areas (SE Turkey), they are found within imbricated slices of a melange complex, known as the Yuksekova Complex. The studied basaltic rocks are common members of this melange complex, and show distinctive features of sources with tholeiitic to tholeiitic-transitional character. Petrography, whole-rock trace element and isotopic data reveal two different compositional groups. Group I is transitional between island arc tholeiites and normal mid-ocean ridge basalt, and Group II includes back-arc (BABB), enriched mid-ocean ridge (E-MORB), and ocean island basalt type (OIB) compositions. According to the known Late Cretaceous stratigraphic ages, the studied basaltic rocks have (Sr-87/Sr-86)(i) = 0.7036660-0.706394, (Nd-143/Nd-144), = 0.512734-0.512927, Pb-208/Pb-204 = 38.3216-39.3400, Pb-207/Pb-204 = 15.5018-15.6262 and Pb-206/Pb-204 = 18.5655-19.3209. In addition, epsilon Nd-i values vary between +3.99 and +8.01 with two-stage T-DM values ranging from 0.25 to 0.59 Ga. In the Sr versus Nd isotope correlation diagram, most samples plot along the mantle array line. In the correlation diagrams of Pb-206/Pb-204 versus Pb-208/Pb-206 and Pb-207/Pb-206, the rock samples also plot nearly on the Northern Hemisphere Reference Line, similar to Atlantic and Pacific Ocean ridge basalts. As a whole, the isotopic data reveal that the studied rocks were derived from a depleted mantle source. When plotted in the conventional tectonic discrimination diagrams based on immobile trace elements, the samples can be related to an arc environment (Group I basalts), and back arc basin (Group II basalts) developed by generation and maturation of the rifted arc in later stages. This interpretation is supported by ages obtained from pillow lava-radiolarian chert associations indicating that the arc stage was realized during the late Cenomanian-early Turonian, followed by Coniacian-early Maastrichtian spreading in a back arc basin within the closing southern branch of Neotethys.
Keywords: melange basalts; petrology; arc-back arc; Southern Neotethys